Changes in activities of antioxidant enzymes in radish (Raphanus sativus) seedlings in response to allelopathic effect of safflower (Carthamus tinctorius) - Marzieh Motamedi; Hassan Karimmojeni; Fatemeh Ghorbani Sini; Mohammad Mahdi Majidi (Universidade de São Paulo, 2023)
Abstract ROS (Reactive Oxygen Species) production is a usual plant reaction to environmental stresses such as allelopathy. Plants possess antioxidant enzymes to scavenge cells and resist against the ROS. This study was conducted to evaluate changes in antioxidant enzymes (CAT, GPX, APX) in radish seedlings in response to allelopathic effect of safflower root and shoot residues grown under normal irrigation and drought stress. Safflower allelopathic effect led to an increase in antioxidant enzymes activities. GPX activity increased more than CAT and APX. Radish seedlings exposed to safflower residue grown under drought stress showed more antioxidant enzymes activities. Root residues enhanced the activities of antioxidant enzymes greater than shoot. Seedlings exposed to root residues grown under drought stress had the highest level of antioxidant enzymes activities.